High Temperature Characteristics of GaN-Based Inverter Integrated With Enhancement-Mode (E-Mode) MOSFET and Depletion-Mode (D-Mode) HEMT - Xu, Zhe; Wang, Jinyan; Yong Cai; Liu, Jingqian; Zhen Yang; Li, Xiaoping; Wang, Maojun; Min Yu; Xie, Bing; Wu, Wengang; Ma, Xiaohua; Zhang, Jincheng; et al. (IEEE ELECTRON DEVICE LETTERS, 2014)
High temperature characteristics of GaN-based inverter is presented from room temperature (RT) to 300 degrees C, which is integrated with enhancement-mode MOSFET and depletion-mode HEMT. At 300 degrees C, the fabricated inverter operates properly at a supply voltage (V-DD) of 7 V with 6.5 V for logic voltage swing, 3.3 V for threshold voltage (V-TH), 2.4 V for logic-low noise margin (NML), and 3.4 V for logic-high noise margin (NMH). Meanwhile, the inverter exhibits small variations from RT to 300 degrees C in terms of logic voltage swing, V-TH, NML, and NMH with the maximum relative variations of 2.2%, 5.7%, 12.9%, and 4.9% in such temperature range, respectively.